Assessing the suitability of fly ash geopolymers for high temperature applications - Rickard, William D. A. (Curtin University, 2012)
Geopolymers are an inorganic polymer synthesised from the dissolution and polycondensation of aluminosilicates in alkaline solutions under hydrothermal condition, yielding an amorphous, three-dimensional polymeric framework (Davidovits, 1991). They are a broad class of binding material with applications that range from conventional concrete to high tech, light weight composites for use in aviation. Geopolymers have also shown promise for use in high temperature applications, such as fire proof coatings, structural concrete in fire prone areas and thermal insulation for refractory type applications, due to their intrinsic thermal stability (Barbosa and MacKenzie, 2003a).This thesis reports on an investigation into the thermal performance of geopolymers synthesised from a range of fly ashes in order to assess their suitability for use in high temperature applications. Five fly ashes from Australian power stations with contrasting chemical properties were used in the study. Geopolymers were synthesised from each of the fly ashes using sodium silicate or sodium aluminate solutions in order to achieve a set range of Si:Al compositional ratios. Thermal analysis was conducted up to 1000 °C using a constant heat rate as well as a heating regime that simulated the conditions during a fire.The fly ashes were characterised in terms of elemental composition, phase composition, particle size, density and morphology prior to being used to synthesise geopolymers. It was determined that only a portion of each of the fly ashes was available for geopolymerisation and that the reactive Si:Al ratio (amorphous Si:Al ratio) varied greatly between the fly ashes. Collie and Port Augusta fly ashes had relatively low reactive Si:Al ratios (1.15 and 1.84, respectively) whereas Eraring, Tarong and Bayswater fly ashes had high Si:Al ratios (4.98, 8.84 and 7.49, respectively). All of the fly ashes had a predominantly spherical morphology, characteristic of fly ashes, though only the Collie and Port Augusta fly ashes had a significant portion of sub 5 μm particles.The thermo-physical, mechanical and micro-structural properties of the geopolymers made from each of the fly ashes are presented and the effect of the source fly ash characteristics on the hardened product is discussed. The results varied greatly with fly ash source and the most influential fly ash characteristic was the reactive Si:Al ratio. Fly ashes with a high reactive Si:Al ratio (≥5) were sodium aluminate activated and produced geopolymers with low to moderate as-cured compressive strengths but exhibited excellent dimensional stability during heating and greater compressive strengths after heating. Fly ashes with a low reactive Si:Al ratio (<2) were sodium silicate activated and produced geopolymers with high as-cured compressive strengths but exhibited poor dimensional stability during heating and greatly reduced compressive strengths after heating. All samples exhibited strength improving microstructural changes such as improved inter-particle bonding due to sintering after firing. However, the instability of non geopolymer phases during high temperature exposure led to strength losses in some samples depending on the type and composition of the activating solution.Geopolymers from three of the fly ashes were assessed for their performance upon exposure to a simulated fire. Solid and low density foamed variants (ρ ≈ 0.9 g cm-3, k ≈ 0.3 W m-1K-1) of the mixes were used for fire testing. Fire ratings of between 60 and 90 minutes for a sample thickness of 50 mm were achieved. The solid geopolymers exhibited better fire ratings than the low density geopolymers due to their higher water content (as they contained more of the hydrated geopolymer phase). Microstructural analysis of the fire tested samples indicated that the geopolymers were not significantly damaged by dehydration and the fire exposed side exhibited analogous changes to the samples that were gradually heated to 1000 °C.The results in this thesis indicate that fly ash geopolymers have great potential for utilisation in high temperature applications provided they are synthesised from a source material with suitable physical and compositional characteristics.